Correction: Tracking physical breakdown of rice- and wheat-based foods with varying structures during gastric digestion and its influence on gastric emptying in a growing pig model. Issue 13 (26th May 2021) - Nadia, Joanna; Olenskyj, Alexander G.; Stroebinger, Natascha; Hodgkinson, Suzanne M.; Estevez, Talia G.; Subramanian, Parthasarathi; Singh, Harjinder; Singh, R. Paul; Bornhorst, Gail M.
Abstract : Correction for 'Tracking physical breakdown of rice- and wheat-based foods with varying structures during gastric digestion and its influence on gastric emptying in a growing pig model' by Joanna Nadia et al., Food Funct., 2021, DOI: ; 10.1039/D0FO02917C .